Care of the patient with invasive meningococcal disease by prehospital emergency medical service clinicians: a scoping review. Issue 2 (28th February 2020) - Pearce, James; Peters, Micah; May, Nikki; Marshall, Helen; Hein, Cindy; Grantham, Hugh
Abstract : Objective: The objective of this scoping review is to systematically map the literature to identify the scope, depth, key concepts and gaps in the evidence regarding care of the patient with invasive meningococcal disease by emergency medical service (EMS) clinicians. Design: Scoping review. This review is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews reporting guideline. Eligibility criteria: Sources which focused on patients with invasive meningococcal disease (population), where the care of EMS clinicians was the focus (concept), in EMS systems worldwide (context) were eligible for inclusion. Search strategy: This review utilised a comprehensive search strategy including MEDLINE, Embase, Emcare, CINAHL, Scopus, Web of Science, Google Scholar and 'grey' literature databases from 1992 to January 2019. The search also included a Google search, a hand-search of relevant journals, screening of reference lists, contact with authors of included sources and use of social media in an attempt to locate all sources of evidence which fit the inclusion criteria of the review. Two reviewers independently screened sources for inclusion. Results: The search yielded 1803 unique records, of which 10 were included in the synthesis. No original research papers were identified, with all sources classed as either clinical audit or text and opinion literature. The dominant concept throughout the literature is that early antibiotic therapy is critical in the treatment of invasive meningococcal disease. Conclusions: Overall, there is a very narrow scope and shallow depth of literature on the topic of interest. There are gaps in the evidence regarding the care of the patient with invasive meningococcal disease by EMS clinicians. Despite these shortfalls, current consensus-based guidelines should direct clinical practice. Further research is planned to bridge the gaps in knowledge to support best practice.